Anticoagulation in the Older Adult: Optimizing Benefit and Reducing Risk - Ko, Darae; Hylek, Elaine M. (Seminars in Thrombosis and Hemostasis, 2014)
The risk for both arterial and venous thrombosis increases with age. Despite the increasing burden of strokes related to atrial fibrillation (AF) and venous thromboembolism (VTE) among older adults, the use of anticoagulant therapy is limited in this population due to the parallel increase in risk of serious hemorrhage. Understanding the risks and their underlying mechanisms would help to mitigate adverse events and improve persistence with these life-saving therapies. The objectives of this review are to: (1) elucidate the age-related physiologic changes that render this high risk subgroup susceptible to hemorrhage, (2) identify mutable risk factors and hazards contributing to an increased bleeding risk in older individuals, and (3) discuss interventions to optimize anticoagulation therapy in this population.
Keywords: aging; anticoagulation; warfarin; atrial fibrillation; stroke; venous thromboembolism